The Philosophy of Nias Megalithic Stones for Catholic Youth in Gunungsitoli - Mendrofa, Kristiana; Marbun, Martina Rosmaulina; Yesudoss, Jeganathan; Harefa, Servasius (Universitas Dharma Wacana, 2025)
This study examines the philosophy of the Nias megalithic stones and their relevance for Catholic Youth (OMK) in the city of Gunungsitoli through a qualitative-ethnographic approach. Data were collected through in-depth interviews with traditional elders, community leaders, and Catholic youth; participatory observation in customary activities and religious devotions; as well as archival documentation, photographs, and field notes. Thematic analysis identified three clusters of values: resilience (perseverance, discipline, hope), community (mutual cooperation, deliberation, communio), and spirituality (awareness of Christ’s presence in cultural history). The findings show that megalithic stones continue to function as cultural archives, centers of social interaction, and pedagogical symbols for the character formation of Catholic youth. Within the framework of inculturation, these values are reinterpreted in catechesis, culturally rooted liturgy, and social action, without contradicting the Church’s teaching. The study concludes that faith-culture integration strengthens the dual identity of Catholic youth and encourages their role as agents of change in preserving the megalithic heritage and in pastoral ministry. Recommendations include digital documentation of sites, culturally based youth training, and ongoing collaboration between parishes, schools, and traditional leaders in the region.